Analysis of SARS-CoV-2 in Corneal Tissue of Deceased Asymptomatic Novel Coronavirus Disease 2019 Donors. Issue 12 (28th December 2022) - Mahalingam, Karthikeyan; Angmo, Dewang; Kakkar, Aanchal; Bafna, Rahul Kumar; Sharma, Tushar; Rai, Aishwarya; Agrawal, Sahil; Dar, Lalit; Saxena, Rohit; Titiyal, Jeewan S.; Sharma, Namrata
Abstract : Purpose: The aim of this study was to analyze the presence of the SARS-CoV-2 virus in the corneal tissue of asymptomatic deceased novel coronavirus disease 2019 (COVID-19) patients. Methods: This was a cross-sectional study performed at a tertiary eye hospital. All corneas of the deceased asymptomatic donors who tested positive for SARS-CoV-2 on a nasopharyngeal swab at the time of corneal tissue harvesting were included in the study. Histopathological examination and immunohistochemistry were performed. mRNA in situ hybridization for SARS-CoV-2 was performed in all specimens that showed positive immunostaining. The main outcome measure was the presence of SARS-CoV-2 virus in the corneal tissues. Results: Twenty-two corneal tissues of 11 donors were analyzed. The mean age was 72.2 ± 14.2 years. On histological examination, no signs of inflammation or any other abnormalities were detected in the cornea and adjacent bulbar conjunctiva. Immunohistochemistry revealed faint to moderate cytoplasmic staining in the basal layer of the corneal epithelium in 8 specimens from 5 patients. None of the specimens with positive immunostaining showed the presence of SARS-CoV-2 mRNA. Conclusions: In line with previous studies, our study also reflects the absence of SARS-CoV-2 viral mRNA in corneal tissues of clinically asymptomatic deceased COVID-19 donors, thereby indicating a probable low risk of transmission of the SARS-CoV-2 virus through the transplantation of corneas from donors who tested positive for, but were asymptomatic for COVID-19. In addition, further studies on the subject should include histopathological examination because of the false positive and negative rates of molecular tests.